(untitled) (Revista da Escola de Guerra Naval, 2023)
International law has been barely focused on the reputational status, which may be represented as a complex of attributes based on the perception of the others, that can determine the state’s position in the international arena and cooperation scenarios. Thus, the opportunity of taking an active role in the international agenda makes Brazil and other middle powers and emerging markets as high-value partners, with an increasing and representative participation in international organizations in the last years. In respect to the Brazilian case, those functions that can be cited as determinants of reputation range from the peacekeeping mandates it has detained, to the candidacy as a permanent member of the United Nations Security Council. This paper is focused on providing a conceptual framework to explain the enhancing of one actor’s international reputation based on Peacekeeping missions and considering Andrew Guzman´s typology (2001; 2010; 2011). This theme is an important way of thinking political gains in terms of international competition not only because it elucidates states’ conditions for obtaining success but, also, how eligible they are for projecting themselves besides military strength. In addition, the effectiveness and compliance ratio, either for the Brazilian case or other emerging markets, are not clear to a great part of the analysts. So, under the soft or hard law, the intention is to make an archeology of the reputation model that is connected to political gains in the Brazilian contemporary case, as to expand its international reliability and promote economic odds.